2020
DOI: 10.1186/s12866-020-01759-x
|View full text |Cite
|
Sign up to set email alerts
|

The penile microbiota of Black South African men: relationship with human papillomavirus and HIV infection

Abstract: Background: To date, the microbiota of the human penis has been studied mostly in connection with circumcision, HIV risk and female partner bacterial vaginosis (BV). These studies have shown that male circumcision reduces penile anaerobic bacteria, that greater abundance of penile anaerobic bacteria is correlated with increased cytokine levels and greater risk of HIV infection, and that the penile microbiota is an important harbour for BVassociated bacteria. While circumcision has been shown to significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 63 publications
4
63
0
8
Order By: Relevance
“…This hypothesis is based on the observation that HIV reduces semen microbiota diversity, which is restored after long-term ART, possibly through immune reconstitution (86). We further observed that among the bacterial taxa that were differentially abundant between men with and without HIV infection (e.g., Staphylococcus, Strenotrophominas, Propionibacterium, and Nosocomiicoccus), it was only an unclassified bacterium in the order Actinomycetales that was associated with HIV infection after adjustment for multiple comparisons (53). The association between HIV infection and the relative abundances of certain penile bacteria could mean that such bacteria either increase the risk of HIV infection or occur as a consequence of HIV infection.…”
Section: Potential Role Of the Penile Microbiota In Hiv Acquisitionmentioning
confidence: 71%
See 4 more Smart Citations
“…This hypothesis is based on the observation that HIV reduces semen microbiota diversity, which is restored after long-term ART, possibly through immune reconstitution (86). We further observed that among the bacterial taxa that were differentially abundant between men with and without HIV infection (e.g., Staphylococcus, Strenotrophominas, Propionibacterium, and Nosocomiicoccus), it was only an unclassified bacterium in the order Actinomycetales that was associated with HIV infection after adjustment for multiple comparisons (53). The association between HIV infection and the relative abundances of certain penile bacteria could mean that such bacteria either increase the risk of HIV infection or occur as a consequence of HIV infection.…”
Section: Potential Role Of the Penile Microbiota In Hiv Acquisitionmentioning
confidence: 71%
“…We used a machine learning approach to identify the bacterial taxa that were differentially abundant in men with vs. without HPV and HR-HPV infections. We noted that higher relative abundances of BV-associated bacteria (Prevotella, Peptinophilus, and Dialister) and lower relative abundance of Corynebacterium were distinctively associated with HR-HPV infections (53). It seems, therefore, that there might be a link between Corynebacterium and protection against penile HPV infection.…”
Section: Potential Role Of the Penile Microbiota In Hpv Infectionmentioning
confidence: 76%
See 3 more Smart Citations